(untitled) (Fractal: Journal of Psychology, 2013)
This brief essay seeks to speak on the contributions of some important publications about issues related to mental and behavioral disorders and their linkages with the work. In this regard, it appears that psychology as a science and profession, is faced with many challenges to overcome, which concern both the training of professionals as to their performance in various fields.